SCIENCE FAIR: RELATIONSHIP BETWEEN UNIVERSITY EXTENSION AND TEACHING TRAINING: RELAÇÃO ENTRE A EXTENSÃO UNIVERSITÁRIA E A FORMAÇÃO DOCENTE (Citizenship in Action: Extension and Culture Magazine, 2023)
Scientific discoveries are an important mechanism for the well-being of society, thus, the dissemination of its findings to the population is important and necessary, mainly to encourage the generation of new researchers. The present work was the result of an extension project that aimed to analyze the importance of initial training for undergraduate Chemistry students in the elaboration and participation of a Science Fair through investigative experimentation. Data collection was performed through behavioral observations recorded in a field diary and later discussed among project members. The analysis of the results showed mainly that the students were able to interact better in face of the different proposals presented by the students, serving as an improvement for their future professional career as a teacher and in the student-teacher relationship. Students were able to propose experiments free of their interests and curiosities, and language, at the level of abstraction for elementary school, was important for undergraduates to relate their academic knowledge to the field of work.
Keywords: Scientific divulgation; Initial Teacher Training; Pedagogical practices